A Deep Blue Strong Microcavity Organic Light‐Emitting Diode Optimized by a Low Absorption Semitransparent Cathode and a Narrow Bandwidth Emitter. Issue 4 (15th February 2021) - Kim, Seong Keun; Park, Mi Jin; Pode, Ramchandra; Kwon, Jang Hyuk
Abstract : Herein, deep blue strong microcavity top‐emitting organic light‐emitting diodes (TEOLEDs) optimized by a low absorbed silver cathode and a narrow bandwidth emitter are reported for realizing high‐efficiency and narrow spectral characteristics. Usually, the Mg:Ag cathode is widely used as a semitransparent cathode in TEOLED devices due to its favorable reflectivity and proper electron injection ability. However, the high extinction coefficient of Mg causes a decrease in the microcavity effect, causing a low optical efficiency of devices. A Ag cathode is applied as a semitransparent cathode to modify the high absorption property for a strong microcavity blue OLED. At optimal conditions, the optically calculated device efficiency of TEOLEDs using a BPPyA emitter is 70.2 and 91.1 cd (A * y) −1 for Mg:Ag and Ag TEOLEDs, respectively. To further improve the device efficiency, an alternative emitter (DABNA‐NP‐TB) is applied which has a narrow bandwidth of 25 nm. The optically calculated efficiency enhancement in the TEOLED is about 23% compared with a control emitter, which is well correlated with the result of fabricated TEOLEDs. Abstract : A blue top‐emitting organic light‐emitting diode with a high efficiency and good color purity is reported. To enhance the device efficiency, a Ag cathode and a narrow bandwidth emitter are applied. The optical simulation results are almost matched with measured device characteristics. Finally, the significant efficiency enhancement of about 1.6 times is noted in the modified device compared with a Mg:Ag cathode device.